Vigilance and tax fraud in early modern Catalonia. - Torra-Prat, Ricard (Social History, 2024)
This article uses the concept of 'cultures of vigilance' (vigilanzkulturen) as an analytical tool to shed light on how early modern Catalan citizens interacted with public institutions in relation to the fight against tax fraud. By studying the surveillance mechanisms used by fiscal authorities in both local and regional scenarios, the article shows how private individuals, guilds, tax farmers and public officials collaborated in partnership to create a system of vigilance in which everybody was surveilling and under surveillance using direct and indirect methods. For public officers and institutions to benefit from practices of vigilance, citizens had to be genuinely willing to collaborate, and the article thus points towards the existence of a deeply rooted symbiosis between citizens and the state in early modern Catalonia under the Spanish monarchy.